But for p 6 1 we can easily check that s k z k 1 1 x

• 62

This preview shows page 41 - 44 out of 62 pages.

But for p 6 = 1 we can easily check that S k = Z k 1 1 x p d x = 1 p - 1 1 - 1 k p - 1 ,
42 while for p = 1 we have S k = Z k 1 1 x d x = log( k ) . (Here log( · ) denotes the natural logarithm.) We then see that the sequence { S k } converges for p > 1 and diverges for p 1. The same is thereby true for the p -series. 3.6. Alternating Series. Until now we have only studied convergence tests for nonnegative series. The underlying tool has been the Monotonic Sequence Theorem (Proposition 2.10), which was used to prove Proposition 3.3. Here we use the Monotonic Sequence Theorem to obtain the following characterization of convergence for a special class of series with alternating sign. Proposition 3.10. (Alternating Series Test) Let { a k } be a positive, nonincreasing sequence in R . Then X k =0 ( - 1) k a k converges ⇐⇒ lim k →∞ a k = 0 . Proof. The direction = is just Proposition 3.2 (Divergence Test). To prove the other direction, let s n = n X k =0 ( - 1) k a k . First, the picture is that { s 2 k } k N is nonincreasing , while { s 2 k +1 } k N is nondecreasing , and that s 2 k > s 2 j +1 for every j, k N . Indeed, the first two assertions follow because s 2 k +2 - s 2 k = a 2 k +2 - a 2 k +1 0 , s 2 k +3 - s 2 k +1 = - a 2 k +3 + a 2 k +2 0 . Next, because s 2 k > s 2 k +1 for every k N , for any j k we have s 2 k > s 2 k +1 s 2 j +1 , s 2 j s 2 k > s 2 k +1 . The result follows by exchanging j and k in the last inequality. The monotonic subsequences { s 2 k } and { s 2 k +1 } are thereby bounded below and above respectively. By the Monotonic Se- quence Theorem they therefore converge. Let s = lim k →∞ s 2 k , s = lim k →∞ s 2 k +1 . Then s - s = lim k →∞ ( s 2 k - s 2 k +1 ) = lim k →∞ a 2 k +1 = 0 , whereby s = s . The last step is to show that this fact implies that { s k } converges. This is left as an exercise. Examples. X k =1 ( - 1) k k p converges for p > 0 , X k =2 ( - 1) k log( k ) converges .
43 3.7. Absolute Convergence. The Monotonic Sequence Theorem has been the tool underlying all the convergence tests we have studied so far. We now use the Cauchy criterion to establish a test that does not require the series to be nonnegative. Proposition 3.11. (Absolute Convergence Test) Let { a k } be a real sequence. Then X k =0 | a k | converges = X k =0 a k converges . Proof. Let { p n } and { q n } be the sequences of partial sums given by p n = n X k =0 | a k | , q n = n X k =0 a k . By hypotheses { p n } is convergent, and thereby Cauchy. The idea of the proof is to show that { q n } is Cauchy, and thereby convergent. The key to doing so is the fact that for every m, n N we have the inequality | q n - q m | ≤ | p n - p m | . This is trivially true when m = n . When n > m the triangle inequality yields | q n - q m | = n X k = m +1 a k n X k = m +1 | a k | = | p n - p m | . The case n < m goes similarly. Let > 0. Because { p n } is Cauchy there exists an N N such that m, n N = ⇒ | p n - p m | < . Because | q n - q m | ≤ | p n - p m | , we immediately see that m, n N = ⇒ | q n - q m | < .
• • • 